Molecular Analysis of S-morphology Aflatoxin Producers From the United States Reveals Previously Unknown Diversity and Two New Taxa - Singh, Pummi; Callicott, Kenneth A.; Orbach, Marc J.; Cotty, Peter J. (Frontiers in Microbiology, 2020)
Aflatoxins are highly toxic carcinogens that detrimentally influence profitability of agriculture and the health of humans and domestic animals. Several phylogenetically distinct fungi within Aspergillus section Flavi have S morphology (average sclerotial size < 400 µm), and consistently produce high concentrations of aflatoxins in crops. S-morphology fungi have been implicated as important etiologic agents of aflatoxin contamination in the United States (US), but little is known about the diversity of these fungi. The current study characterized S-morphology fungi (n = 494) collected between 2002 and 2017, from soil and maize samples, in US regions where aflatoxin contamination is a perennial problem. Phylogenetic analyses based on sequences of the calmodulin (1.9 kb) and nitrate reductase (2.1 kb) genes resolved S-morphology isolates from the US into four distinct clades: 1) Aspergillus flavus S-morphotype (89.7%); 2) A. agricola sp. nov. (2.4%); 3) A. texensis (2.2%); and 4) A. toxicus sp. nov. (5.7%). All four S-morphology species produced high concentrations of aflatoxins in maize at 25°C, 30°C and 35°C, but only the A. flavus S-morphotype produced unacceptable aflatoxin concentrations at 40°C. Genetic typing of A. flavus S isolates using 17 simple sequence repeat markers revealed high genetic diversity, with 202 haplotypes from 443 isolates. Knowledge of the occurrence of distinct species and haplotypes of S-morphology fungi that are highly aflatoxigenic under a range of environmental conditions may provide insights into the etiology, epidemiology, and management of aflatoxin contamination in North America.